22‐2: An Ultra‐thin Flexible Thin Film Encapsulation Structure with High Transmittance and Reliability. Issue 1 (25th September 2020) - Wang, Youwei; Sun, Tao; Qin, Chengjie; Zhang, Song; Wang, Tao; Zhang, Ziyu; Hong, Rui
Abstract : We report an ultra‐thin film encapsulation structure composited of atomic layer deposition layer and organic layer, which show a 4% improvement in transmittance with tandem TFE film, especially for blue region (94% up to 99%) and a 60% thickness decrease of inorganic layer. The TFE film shows an excellent flexibility performance, there was no crack after 60/90 500 hour static bending for R2. It also shows good reliability, storage for 85/85 500h, which indicates a great potential application in flexible display, especially for bendable display.